1989
DOI: 10.1002/adma.19890010705
|View full text |Cite
|
Sign up to set email alerts
|

Structure of anodic oxide coatings on aluminum

Abstract: Porous surface coatings on aluminum are produced by anodic oxidation in acid electrolytes.[" Pore sizes (10-250 nm) as well as pore densities (10'2-1015 m-') are mainly controlled by the anodizing voltage; the thickness of the layers may reach more than 100 pm and is determined by the amount of charge transferred. The remarkably uniform array of the pores in the centers of the almost hexagonally shaped cells makes the films of interest for application in the field of synthetic membranes and as supports for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The density of amorphous alumina has been reported by several groups (Oka et al, 1979;Kniep et al, 1989;Lee et al, 1995;Wang et al, 1997;Momida et al, 2006;Gorham et al, 2014). Kniep et al (1989) suggested that the density of pure amorphous alumina was 3.3 g cm −3 . Lee et al (1995) reported the density of alumina film deposited by magnetron techniques was 3.4 g cm −3 .…”
Section: Densitymentioning
confidence: 94%
“…The density of amorphous alumina has been reported by several groups (Oka et al, 1979;Kniep et al, 1989;Lee et al, 1995;Wang et al, 1997;Momida et al, 2006;Gorham et al, 2014). Kniep et al (1989) suggested that the density of pure amorphous alumina was 3.3 g cm −3 . Lee et al (1995) reported the density of alumina film deposited by magnetron techniques was 3.4 g cm −3 .…”
Section: Densitymentioning
confidence: 94%